Sosialisasi Penentuan Siswa Terbaik pada SMAN 4 Padang Menggunakan Metode WASPAS - Guswandi, Dodi; Hafizh, M; Novita, Triana (LPPM Universitas Dharma Andalas, 2025)
At SMAN 4 Padang, the process of determining the best students is still carried out manually, does not use a computerized system and there is no decision-making method for analyzing data. As a result, this process is often very long and the results of decisions are not precise and accurate. The purpose of this Community Service (PKM) is to provide socialization to SMAN 4 Padang in making decisions appropriately and accurately using the Weighted Aggregated Sum Product Assessment (WASPAS) method, this method combines two models, namely the weighted sum model (WPM) and the weighted product model (WCM). The system implementation into the application uses the PHP programming language and MySQL database. The assessment criteria used are Attendance (C1), Personality (C2), Achievement (C3), Extracurricular (C4), and Final Report Value (C5). Several samples of data have been tested, where students with code A2 get the highest score, which is 0.7566 are declared the best students. After socializing and implementing the new system design, it can make it easier for SMAN 4 Padang schools to make decisions quickly, precisely, and accurately.